Insights from case studies into sustainable design approaches in the minerals industry. (15th May 2015) - Corder, G.D.
Highlights: Environmental, community and social factors are increasingly influencing new mining projects. Project development processes need holistic approaches to deal with these complexities. Case studies from applying a holistic framework illustrated typical sustainability benefits. Benefits included water and energy savings, lower capital costs and enhanced capacity building. Abstract: The concept of sustainability, which is now well entrenched in the minerals industry, can be an effective driver for higher levels of innovation. With the minerals industry venturing into riskier locations, new mining projects need to deliver both strong sustainability benefits while meeting the necessary technical and financial requirements. Improved approaches to recycling, resources conservation, energy and water efficiency, greenhouse gas reduction, biodiversity, local enterprise development, and community development programs all meet the aims of good sustainability practice and require innovative techniques to move away from the 'business as usual' paradigm. This paper outlines the recent developments on the SUSOP sustainability opportunities and risks framework, which utilises the Five Capitals sustainability model, to provide a holistic approach for delivering enhanced environmental, social and community outcomes into mining and minerals projects. Case studies where this framework has been applied are discussed and the key emerging themes such as the benefits of better engagement with local stakeholders, the value from creation of local enterprises, and misperceptions of costs related to sustainability outcomes are highlighted.